Outsider art : spontaneous alternatives - Rhodes, Colin; Thames and Hudson (New York, N.Y. : Thames & Hudson, 2000)
"Outsider Art is the work produced outside the mainstream of modern western art by self-taught, untrained visionaries, spiritualists, eccentric recluses, folk artists, psychiatric patients, criminals and others beyond the imposed margins of society and the art market. Coined by Roger Cardinal in 1972, the term in English derived from Jean Dubuffet's "Art Brut"--Literally "raw art," "uncooked" by culture, unaffected by fashion, unmoved by artistic standards. In this indispensable book Colin Rhodes surveys the history and reception of Outsider Art - first championed by Dubuffet and the Surrealists, now appreciated by a wide public - while providing fresh insights into the achievements of both major figures and newly discovered artists. From spirit-guided Madge Gill to schizophrenic Adolf Wolfli, these individuals passionately and obsessively pursue the pictorial expression of their vision."--Jacket.
-- Art brut -- Art by the insane -- Alternative worlds -- Self-taught visionaries -- Other positions.
Includes bibliographical references (pages 218-219) and index.
Keywords: Outsider art; Art brut; Art, Modern -- 20th century